Impact of expansion level on flowfield with sudden expansion at supersonic regimes - Faheem, Mohammed; Ridwan, R; Rayid, Muneer; Delvi, Hamza Afser; Khan, Sher Afghan (Elsevier Ltd, 2021)
This paper aims to assess the control mechanism’s efficiency and flow pattern in the pipe. The flow was investigated for Mach numbers M = 1.25, 1.3, 1.48, 1.6, 1.8, 2.0, 2.5, and 3.0 for a step height of 3 mm. The NPRs of the tests were from 11 to 3. The flow revealed the minimum duct requirement for a given Mach number and NPR as L = 2D. Only some selected cases where the control mechanism impacts considerably are presented. In most of the cases, the flow field was the same. There is a reversal in control in the flow field; only such cases are discussed. At low Mach numbers, the flow regulator raises the pressure, and for the rest of the Mach numbers, t